PENGARUH SUHU PREHEAT DAN VARIASI ARUS PADA HASIL LAS TIG ALUMINIUM PADUAN TERHADAP KEKUATAN TARIK DAN KEKERASAN - Nurfi Ahmadi (Institut Teknologi Dirgantara Adisutjipto, 2016)
Aluminium has a good nature; corrosion-resistant, lightweight, and able to be recycled. But the connection with welding aluminum is difficult to do so we need the right way this study aims to determine the characteristics of the results of weld aluminum with large variations in preheat temperature and current. Aluminum Alloy AA 3003 TIG welded with Filler ER 5356, a variation current 110 A, 130 A, 140 A and preheat temperature of 75 degree celcius, 125 degree celcius, 175 degree celcius, then welds tested tensile, hardness, and microstructure. The results showed that the variation o f the current 110 A with a preheat temperature of 175 degree C has the highest tensile strength and hardness.